PARENTING PARENTS ON THE OCCURANCE OF ACUTE RESPIRATORY INFECTION (ARI) IN CHILDREN AGED TODDLER 2-3 YEARS (Studied In Sub-Village Of Bandung Gebangmalang Village Of Bandung District Of Diwek Jombang Regency) - Yulita Fatimah; . Muarrofah; Dwi Puji (Jurnal Keperawatan, 2012)
In general, the responsibility of parenting is the duty of both parents but the reality of the matter at the present time is reduced concern of parents on parenting because they both work. This causes the limited interaction of parents with their children, so that in the care of a healthy hygienic behavior in children less attention. As a result, children are susceptible to bacteria, viruses, and other germs, and until there was the problem of disease in children, especially ill ARI. This study aimed to analyze the pattern of parenting to the occurrence of acute respiratory infection (ARI) in children This research design is survey cross sectional. The population in this research was the entire parents whose children ages 2-3 years who had ever experienced acute respiratory infection (ARI) in sub-village of Bandung Gebangmalang, village of Bandung, district of Diwek, Jombang regency with total 41 respondents and the sample were 37 respondents. Sampling technique used was simple random sampling. This research variabel was the pattern of parenting and occurance of ARI. The collection of data obtained by questionnaire and data analysis includes editing, coding, scoring, tabulating, and spearman rank’s statistic test with an error rate (α) 0,05. Results research influence parenting parents with occurance of ARI in children aged toddler 2-3 years was obtained almost a half of respondents’ parenting pattern was less 46% and most of the occurrence of acute respiratory infections (ARI) was often 70,3%. The results of Spearman rank’s test was ontained p value < α (0,000 < 0,05) so H1 accepted. There is effect of parenting parents on occurance of acute respiratory infection (ARI) in children aged toddler 2-3 years in sub-village of Bandung Gebangmalang village of Bandung district of Diwek Jombang regency. So that it is required being conducted a health conseling in order to parents know the best way in parenting, educating and caring children.